The Flexor Pollicis Longus Reflex: Interrater and Intrarater Reliability in Comparison With Established Muscle Stretch Reflexes. (June 2021) - Gladitz, Luisa Marilena; Schöttker-Königer, Thomas; Sturm, Christian; Gutenbrunner, Christoph; Ranker, Alexander
Abstract : Objective: The aim of this study was to investigate the interrater reliability and intrarater reliability of the flexor pollicis longus muscle stretch reflex (FPLR) and compare it with clinically established reflexes. Design: A total of 71 healthy volunteers participated. The FPLR, biceps reflex, brachioradialis reflex, and patellar tendon reflex of each participant were tested bilaterally and rated by eight examiners (four experienced, four inexperienced). For intrarater reliability evaluation, five examiners rated the reflexes of four volunteers at four different points in time. Results: Analysis of the interrater reliability with Gwet's AC1 demonstrated almost perfect agreement for FPLR (Gwet's AC1 = 0.90), biceps reflex (Gwet's AC1 = 0.90), and patellar tendon reflex (Gwet's AC1 = 0.95) when using binary data (reflex present vs. absent). Only fair agreement was found for the brachioradialis reflex (Gwet's AC1 = 0.56). Experienced raters had a higher agreement than inexperienced raters did when rating the biceps reflex and the patellar tendon reflex. The intrarater reliability was almost perfect for the patellar tendon reflex (Gwet's AC1 = 0.94), followed by the FPLR (Gwet's AC1 = 0.83) with substantial agreement and the biceps reflex (Gwet's AC1 = 0.57) with moderate agreement. Conclusion: The FPLR is a reliable diagnostic neuromuscular test and may therefore be useful in the clinical examination for C8/T1 nerve root lesions or pathologies of the interosseous anterior nerve. To Claim CME Credits: Complete the self-assessment activity and evaluation online at http://www.physiatry.org/JournalCME CME Objectives: Upon completion of this article, the reader should be able to: (1) Elicit the flexor pollicis longus muscle stretch reflex; (2) Discuss the disadvantage of kappa statistics in assessing the interrater reliability when the prevalence of the studied trait is very high or very low; and (3) Name the spinal nerves involved in the innervation of the flexor pollicis longus muscle. Level: Advanced Accreditation: The Association of Academic Physiatrists is accredited by the Accreditation Council for Continuing Medical Education to provide continuing medical education for physicians. The Association of Academic Physiatrists designates this Journal-based CME activity for a maximum of 1.0 AMA PRA Category 1 Credit(s) ™. Physicians should only claim credit commensurate with the extent of their participation in the activity. Abstract : Supplemental digital content is available in the text.